Large-Scale Post-Crisis Corporate Sector Restructuring - Stone, Mark (IMF Policy Discussion Papers; Policy Discussion Paper, 2000)
This paper summarizes the objectives, tasks, and modalities of large-scale, post-crisis corporate restructuring based on nine recent episodes with a view to organizing the policy choices and drawing some general conclusions. These episodes suggest that government-led restructuring efforts should integrate corporate and bank restructuring in a holistic and transparent strategy based on clearly defined objective and including sunset provisions.